ENVIRONMENTAL RADIO ACTIVITY IN THE MALAPPURAM DISTRICT, KERALA, INDIA - USING BIOINDICATOR SPECIES - CHINNADURAI, G.; BASITH, O.; MURUGESAN, V.; THASNEEM, M. MOHAMED; KRISHNAMOORTHY, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The present work on the natural radioactivity such as Gross alpha, Polonium-210 and lead-210 in the lichens of Malappuram district has been undertaken on the radiation profile of Malappuram district, Kerala. To measure the radioactivity activates in lichens by using the Radiation Counter System (Nucleonex- RC 605A). The gross alpha level was 2.26 mBq/g to 5.88 mBq/g with the mean value of 3.52 mBq/g. The activity of 210Po was 1.10 Bq/kg to 3.37 Bq/kg with the mean value of 1.44 Bq/kg. It has been observed that the concentration210Pb in the lichen sample was 1.15 Bq/kg to 2.10 Bq/kg with the mean value of 1.33 Bq/kg. During the survey period an irregular distribution of radiation profile was observed in the lichen species of Malappuram district.